Winning by deemphasizing winning: establishing climates for moral development in sports - Nielsen, L. (The Sport Journal, 2014)
Purpose: This article was adapted from an unpublished essay previously submitted by the author as a course requirement for SAB 634: Ethics in Sports at the United States Sports Academy in Daphne, Alabama. The essay is intended to provide coaches and athletics administrators-specifically those operating within the frameworks of high school, club, and non-profit-generating collegiate programs-with a sound functional overview of existing research related to the influence of the program climate on the moral development of athletes and to offer suggestions for the implementation of research-supported techniques aimed at eliciting high levels of positive moral development. Methods: A broad range of existing literature related to the moral development of athletes was compiled, examined, analyzed, and disseminated. Results: The examined research findings suggest that moral development is rooted in emotional contexts and develops from a high level of externalization toward autonomy. Furthermore, existing research clearly supports a strong positive correlation between the social environment, the motivational orientation of athletes, and moral development. Specifically, coaches who model and support autonomous moral behaviors maintain the most positive influence on the healthy moral development of athletes; and athletes possessing high task-ego goal orientations tend to have the highest levels of moral functioning. Conclusions: Due to their inherently emotional constructs and the progressive development of skills toward autonomy associated with sports, athletics serve as an ideal environment for moral development. By deemphasizing winning as an end goal in order to support task goal orientation and healthy competition, sports programs can effectively promote positive moral development. Applications in Sports: Athletics organizations that claim to exist for the developmental benefit of the participating athletes-specifically non-revenue generating athletics entities—must examine and implement sound research-supported strategies associated with the moral development of athletes. By developing an understanding of the concepts identified and incorporating the practices prescribed within this essay, coaches and athletics administrators may establish sports programs that effectively promote positive moral development.